Energy from waste: a possible alternative energy source for large size municipalities - Eleftheriou, Polyvios (My University, 2007)
The net calorific values and weight composition of solid waste from all the major municipalities of the island of Cyprus were measured. Representative waste samples were collected, processed and tested for energy generation over a complete year. The energy values appear to vary from city to city depending on the season. The total energy that could be recovered from the waste amounted to approximately 8.5% of the total electricity generation of the island of Cyprus.
Keywords: Renewable energy sources; Electricity; Waste products; Power resources